Bifunctional N/O-doped porous carbons:Electron localization enables efficient adsorption and electron delocalization boosts PMS activation - Mingwei Yang; Maoguo Tan; Denghong Zhao; Hang Liu; Hongji Chen; Tao Liao; Jia Zeng; Yanke Jiang; Lixia Guo; Bin Sun; Heyan Jiang (Environmental Research, 2026)

Suppression of the Rhizoma Coptidis-Mediated Antibiotic Cross-Resistance in Staphylococcus aureus Using Radix Paeoniae Rubra - Chaoheng Chen; Yilan Huang; Yanke Liao; Sugui Lan; Zining Liang; Jing Yuan; Qiang Tan (Current Microbiology, 2025)

A tropical Pacific convection ENSO index suitable for measuring the impact of ENSO on the East Asian winter monsoon - Jia Huang; Renhe Zhang; Yanke Tan (Climate Dynamics, 2025)

Role of ocean-atmosphere interaction in intraseasonal variability of summer rainfall over the Indo–Northwest Pacific - Yang Wang; Zhen-Qiang Zhou; Renhe Zhang; Yanke Tan (Climate Dynamics, 2024)

Experiment investigation and theoretical analysis of an improved aluminum alloy gusset joint - Shuxiang Zhang; Qilin Zhang; Yanke Tan; Xinye Li; Zhiqiang Li; Jian Yin (Engineering Structures, 2024)

Comparison of two filter approaches for characterizing boreal summer intraseasonal oscillation - Yang Wang; Zhen-Qiang Zhou; Renhe Zhang; Yanke Tan (Atmospheric Research, 2024)

Interannual variability of surface air temperature over indochina peninsula during summer monsoon onset - Meiru Zhang; Zhen-Qiang Zhou; Renhe Zhang; Yanke Tan; Min Wen (Climate Dynamics, 2023)

Plausible causes of the interdecadal change of the North Pacific teleconnection pattern in boreal spring around the late 1990s - Yuanyuan Guo; Zhiping Wen; Yanke Tan; Xiuzhen Li (Climate Dynamics, 2020)

Correction to: Further inquiry into the interaction between the winter North Pacific storm track and the East Asian trough - Minghao Yang; Chongyin Li; Yanke Tan; Xin Li; Xiong Chen; Peilong Yu (Climate Dynamics, 2020)

Further inquiry into the interaction between the winter North Pacific storm track and the East Asian trough - Minghao Yang; Chongyin Li; Yanke Tan; Xin Li; Xiong Chen; Peilong Yu (Climate Dynamics, 2020)
Based on the daily ERA-Interim reanalysis, interactions between the winter North Pacific storm track (WNPST) and the East Asian trough (EAT) on the interannual scale are further explored from the perspective of energy conversion and the simplified quasi-geostrophic potential vorticity equation. There is a prominent out-of-phase relationship between the EAT and WNPST on the interannual scale. It is baroclinic energy conversion rather than barotropic energy conversion that is the main physical process that the EAT affects the WNPST. When the EAT is intensified, the energy conversion from mean available potential energy to eddy available potential energy decreases; further, the energy conversion from eddy available potential energy to eddy kinetic energy is attenuated, which leads directly to remarkable weakening in the strength of the WNPST in its peak area and the region west of the date line. In addition, when the WNPST is enhanced, the WNPST dynamic forcing contributes to lowering the geopotential height near the EAT and thus profits to recover the strength of the EAT, while the thermal forcing of WNPST is opposite. However, their joint effect is still to strengthen the EAT, indicating that the impact of WNPST dynamic forcing on the EAT is stronger than that of thermal forcing. The interaction between the WNPST and EAT may be a way for the WNPST to maintain itself.

Involvement of MEM1 in DNA demethylation in Arabidopsis - Yanke Lu; Jie Dai; Liu Yang; Yumei La; Shaoxia Zhou; Sheng Qiang; Qianqian Wang; Feng Tan; Yufeng Wu; Weiwen Kong; Honggui La (Plant Molecular Biology, 2020)

Influence of cumulus convection schemes on winter North Pacific storm tracks in the regional climate model RegCM4.5 - Minghao Yang; Yanke Tan; Xin Li; Xiong Chen; Chao Zhang; Peilong Yu (International Journal of Climatology, 2020)
Based on the regional climate model RegCM4.5 driven by National Centers for Environmental Prediction (NCEP) reanalysis, the influence of cumulus convection schemes (CCSs) on the winter North Pacific storm track (WNPST) is investigated. It is found that the climatology, interannual variation, spatial modes and characteristic indices of the WNPST are extremely sensitive to the choice of CCS. Among the selected CCSs, WNPST climatology and interannual variation in the Kuo scheme are better than in other CCSs, with a smaller root mean square error. The WNPST spatial modes and strength indices in the Kuo and Grell schemes are more consistent with NCEP reanalysis. The Kuo scheme has a stronger ability to simulate the WNPST latitude index and the interannual variation of winter characteristic indices. In addition, we attempt to reveal the possible reasons for the different performances of CCSs from the viewpoint of baroclinic energy conversion (BCEC). It is found that the energy conversion from the mean available potential energy to the eddy available potential energy (BCEC1) has no significant difference among the Kuo, Grell and Emanuel schemes, while energy conversion from the eddy available potential energy to eddy kinetic energy (BCEC2) in the Kuo scheme is obviously better than other CCSs, which means that the differences in BCEC2 among these CCSs may be one of the key reasons affecting the simulation results of the WNPST.

Influence of the South Pacific decadal variability on Southeast China rainfall during boreal autumn - Gang Li; Jiepeng Chen; Xin Wang; Yanke Tan (International Journal of Climatology, 2018)
Using observational data and numerical experiments, the decadal relationship between South Pacific and rainfall over southeastern China during boreal autumn is examined. In the observational analyses, it is found that the boreal autumn South Pacific shows significant decadal variability with a significant periodicity of 11–21 years from 1960 to 2000, which is an independent phenomenon in the whole Pacific. This South Pacific decadal variability can induce significant decadal variability of boreal autumn rainfall over southeastern China. When the boreal autumn South Pacific decadal variability is in its positive phase, less rainfall appears over the southeastern China, and vice versa. The possible physical mechanisms are further investigated. It is suggested that the negative sea surface temperature anomalies (SSTA) in the extratropical South Pacific associated with positive phase of South Pacific decadal variability could result in an anomalous anticyclone to the east of Australia. The cross‐equatorial flow over the Maritime Continent and tropical western Pacific is enhanced under the influence of this anomalous anticyclone, favouring the location of western Pacific subtropical high moving more eastwards and then leading to the formation of anomalous cyclone over western North Pacific. To the west flank of this anomalous cyclone is the significantly anomalous northerly, which is favourable for less rainfall over southeastern China. On the other hand, significant negative SSTA appears in the Maritime Continent and tropical western Pacific could cause anomalous sinking motion here, which can further induce anomalous sinking motion over southeastern China through two meridional cells extending from Maritime Continent to southeastern China with a common rising branch over the southern South China Sea, thus resulting in less rainfall over southeastern China. Numerical experiments confirm our observational results.

Remote impact of North Atlantic sea surface temperature on rainfall in southwestern China during boreal spring - Gang Li; Jiepeng Chen; Xin Wang; Xia Luo; Daoyong Yang; Wen Zhou; Yanke Tan; Hongming Yan (Climate Dynamics, 2018)

Error inhomogeneity in the computation of spherical mean displacement - Xuezhong Wang; Banghui Hu; Hong Huang; Ju Wang; Gang Zeng; Yanke Tan; Li Zou (Journal of Meteorological Research, 2017)

Further inquiry into characteristics of MJO in boreal winter - Xiong Chen; Chongyin Li; Yanke Tan (International Journal of Climatology, 2017)
The characteristics of Madden–Julian Oscillation ( MJO ), especially over the equatorial western Pacific, during the boreal winter (November to March) have got a further investigation based on the reanalysis data. The MJO activity prevails over the equatorial Indian Ocean and western Pacific and its main active centres are in the Southern Hemisphere. The MJO also has the highest percentage in the atmospheric variability and strong interannual variability here. The MJO over the equatorial western Pacific shows a prominent interannual variability with a period of 2–8 years and an interdecadal variability with a period of 12–16 years. These variabilities of MJO are closely related to the intensity and duration of strong discrete MJO events over there. During the equatorial western Pacific MJO activity strong winter, the MJO is intensified throughout the tropics and its eastward propagation is more continuous, more coherent, and further east. Anomalous ascending motion and moisture convergence over the equatorial western Pacific could enhance the Walker circulation over the equatorial Pacific and favour the activity of MJO over the equatorial western Pacific. The further eastward propagation of MJO in strong MJO activity winter is mainly due to the strong moistening at the lower troposphere to the east of the MJO convection centre. This moistening is dominated by the vertical advection of moisture. In weak MJO activity winter, the above characteristics are reversed. Furthermore, the MJO activity over the Indian Ocean and Pacific has undergone several interdecadal changes in both of its intensity and propagation during the past 150 years.

Impact of East Asian winter monsoon on MJO over the equatorial western Pacific - Xiong Chen; Chongyin Li; Jian Ling; Yanke Tan (Theoretical and Applied Climatology, 2017)

Diagnosis of moist vorticity and moist divergence for a heavy precipitation event in Southwestern China - Gang Li; Daoyong Yang; Xiaohua Jiang; Jing Pan; Yanke Tan (Advances in Atmospheric Sciences, 2017)

The seasonal variations in the significant wave height and sea surface wind speed of the China’s seas - Chongwei Zheng; Jing Pan; Yanke Tan; Zhansheng Gao; Zhenfeng Rui; Chaohui Chen (Acta Oceanologica Sinica, 2015)

The influence of El Niño on MJO over the equatorial pacific - Xiong Chen; Chongyin Li; Yanke Tan (Journal of Ocean University of China, 2015)

Scoring the collective effects of SNPs: association of minor alleles with complex traits in model organisms - DeJian Yuan; ZuoBin Zhu; XiaoHua Tan; Jie Liang; Chen Zeng; JieGen Zhang; Jun Chen; Long Ma; Ayca Dogan; Gudrun Brockmann; Oliver Goldmann; Eva Medina; et al. (Science China Life Sciences, 2014)

The interdecadal changes of south pacific sea surface temperature in the mid-1990s and their connections with ENSO - Gang Li; Chongyin Li; Yanke Tan; Tao Bai (Advances in Atmospheric Sciences, 2014)

Impacts of the central and eastern Pacific types of ENSOon sea surface temperature in the South Pacific - Gang Li; Chongyin Li; Yanke Tan; Jing Pan (Theoretical and Applied Climatology, 2013)

Seasonal evolution of dominant modes in south pacific SST and relationship with ENSO - Gang Li; Chongyin Li; Yanke Tan; Tao Bai (Advances in Atmospheric Sciences, 2012)

On the differences and climate impacts of early and late stratospheric polar vortex breakup - Lin Li; Chongyin Li; Jing Pan; Yanke Tan (Advances in Atmospheric Sciences, 2012)

Meridional wind stress anomalies over tropical pacific and the onset of El Niño. Part I:Data analysis - Zhang Renhe; Zhao Gang; Tan Yanke (Advances in Atmospheric Sciences, 2001)